Uma análise crítica do termo organizações intensivas em conhecimento - Nadai, Fernanda C. de (Revista Gestão da Produção Operações e Sistemas, 2006)
The intense competition among the markets requires from the companies ability to develop and manageefficiently their financial, structural or personnel resources. In the literature, there is the prevalence ofapproaches considering the capital as the main resource to be managed. However, in the economy based oninformation and intensive service, efficiency, flexibility, innovation and qualified personnel become essentialaspects so that the organizations maintain competitive. Facing this reality, knowledge must be considered avaluable and strategic resource in the establishment of a sustainable competitive advantage in theorganizations. However, regarding the intensive organizations in knowledge, it becomes an essential feature.The proposal of this paper is to incite a discussion on what really determines that a company be intensive inknowledge, a term used to classify this type of organization in some literature papers in order to classify thistype of organization. Some organizational characteristics which could determine this classification arepresented here: performed activities, personnel, operating market, products, services and managementpractices. Based on such characteristics, it is possible to define an intensive organization in knowledge.Keywords: Knowledge; Strategic resource; Intensive organization in knowledge.